Frictional strength of wet and dry montmorillonite. Issue 5 (6th May 2017) - Morrow, C. A.; Moore, D. E.; Lockner, D. A.
Abstract: Montmorillonite is a common mineral in fault zones, and its low strength relative to other common gouge minerals is important in many models of fault rheology. However, the coefficient of friction, μ, varies with degree of saturation and is not well constrained in the literature due to the difficulty of establishing fully drained or fully dried states in the laboratory. We measured μ of both saturated and oven‐dried montmorillonite at normal stresses up to 700 MPa. Care was taken to shear saturated samples slowly enough to avoid pore fluid overpressure. For saturated samples, μ increased from 0.10 to 0.28 with applied effective normal stress, while for dry samples μ decreased from 0.78 to 0.45. The steady state rate dependence of friction, ( a − b ), was positive, promoting stable sliding. The wide disparity in reported frictional strengths can be attributed to experimental procedures that promote differing degrees of partial saturation or overpressured pore fluid conditions. Plain Language Summary: Montmorillonite is a common mineral in fault zones, and its low strength relative to other common fault minerals is important in many models of fault rheology. However, the coefficient of friction varies with degree of saturation and is not well constrained in the literature due to the difficulty of establishing fully drained or fully dried states in the laboratory. In this study, the coefficient of friction, μ, of both saturated and oven‐dried montmorillonite was carefully measured in order to avoid pore fluid overpressure. For saturated samples, μ increased from 0.10 to 0.28 with applied effective normal stress, while for dry samples μ decreased from 0.78 to 0.45. The steady state rate dependence of friction, ( a − b ), was positive, promoting stable sliding. The wide disparity in reported frictional strengths can be attributed to experimental procedures that promote differing degrees of partial saturation or overpressured pore fluid conditions. Key Points: The coefficient of friction of drained, water‐saturated montmorillonite ranges from 0.10 at low effective normal stress to 0.28 at 600 MPa Water reduces the friction of montmorillonite to less than 20% of dry friction at low stress and around 50% of dry friction at 600 MPa We see no plastic limit to shear strength in water‐saturated montmorillonite at effective normal stress up to 600 MPa